Business Performance Improvement Model Through Entrepreneurial Skills and Benchmarking Mediated by Innovation Performance of MSMEs in the Culinary Creative Industry Sub-Sector in West Java Province - Syahyono, S (Politeknik APP Jakarta, 2022)
This study aimed to analyze the effect of Entrepreneurship Skills and Benchmarking on the Business Performance of Culinary MSMEs mediated by Innovation Performance. This research is descriptive-verificative with survey research, the approach in this study used a descriptive-quantitative approach. There were 338 observation units (respondents) who filled out the questionnaire. The sampling technique used was proportional random. Descriptive analysis and verification analysis were used to process the data. The results of this study showed that low innovation performance, low entrepreneurial skills and the application of benchmarking were the causes of low culinary business performance achievements in West Java, . Entrepreneurial competence must be improved in order to have a greater impact on innovation performance that has an impact on continuous performance improvement.